Porphyromonas gingivalis may interfere with conception in women - Susanna Paju (Journal of Oral Microbiology, 2017)
In this observational and prospective study, we investigated if microbiological and serological markers of periodontitis associated with conception in 256 non-pregnant women (Mage = 29.2 years; range 19–42 years). Clinical oral and gynecological examinations were performed, major periodontal pathogens in the saliva were detected, and serum and saliva antibodies against major periodontal pathogens were analyzed. The follow-up period for becoming pregnant was 12 months. Porphyromonas gingivalis was significantly (p = 0.032) more frequently detected in the saliva among those who did not become pregnant (8.3%) than among those who became pregnant (2.1%). The median levels of salivary P. gingivalis immunoglobulin A (IgA; p = 0.006) and IgG (p = 0.007) antibodies were higher among those who did not become pregnant compared to those who became pregnant. Hazard ratios (HR) for not becoming pregnant were HR = 3.75 (95% confidence interval [CI] 1.01–13.9; p = 0.048) if the subject was polymerase chain reaction–positive for P. gingivalis with high salivary antibodies against it, and HR = 1.62 (95% CI 1.03–2.54; p = 0.035) if she had high levels of serum P. gingivalis IgA and signs of periodontal infection. P. gingivalis associated with no success in getting pregnant.